CARACTERÍSTICAS FÍSICO-QUÍMICAS DE GEOPRÓPOLIS DE Melipona fasciculata Smith (Tiúba) PRODUZIDO NO ESTADO DO MARANHÃO - Dutra, Richard Pereira (2006)
Pharmacognostic evaluation of geopropolis of Melipona fasciculata Smith at Baixada Maranhense, Brazil . Melipona fasciculata Smith is a native, social, stingless bee specie that produces wax, honey and geopropolis. This work aimed to do a pharmacologic evaluation of Melipona fasciculata geopropolis, collected in beehives in the municipal districts of Arari, Sao Bento and Sao Joao Batista, in Baixada Maranhense, in the state of Maranhão, seeking to obtaining basis for the quality control and standardization of the product. The methodology used included the accomplishment of sensorial analyses, chemical approach, chromatographic profiles and determination of the flavonoids tenors. The results demonstrate that the geopropolis have sensorial characteristics similar to the ones found for propolis of Apis mellifera, presence of phenolic compounds in larger concentration, besides substances of the class of the terpenes and saponins and absence of alkaloids. The chromatographic profiles indicated that the composition and concentration of the chemical substances are different among the samples. The flavonoids tenors ranging between 0.17-2.6%. The tenor for most of the samples presented values above the minimum demanded by the Brazilian legislation for propolis of Apis mellifera. The found data suggest that the qualitative and quantitative variations of flavonoids and other chemical substances in geopropolis are strongly affected for the flora visited by the bees, geographical area and environmental factor.